Real‐world resource use and costs of adjuvant treatment for stage III colon cancer. (25th December 2013) - van Gils, C.W.M.; de Groot, S.; Tan, S.S.; Redekop, W.K.; Koopman, M.; Punt, C.J.A.; Uyl‐de Groot, C.A.
<x xml:space="preserve">Abstract</x> Since the generalisability of trial‐based economic evaluations may be limited, there is an increasing focus on real‐world cost‐effectiveness. Real‐world studies involve evaluating the effects and costs of treatments in daily clinical practice. This study reports on the real‐world resource use and costs of adjuvant treatments of stage III colon cancer in a population‐based observational study. Analyses were based on a detailed retrospective medical chart review which was conducted for 206 patients with colon cancer treated in 2005 and 2006 in the Netherlands. Mean total costs per patient were €9681 for 5‐FU/LV, €9736 for capecitabine, €32 793 for FOLFOX and €18 361 for CAPOX. Drug costs and the costs related to hospitalisations for chemotherapy administration were the main cost drivers. We identified a potential for substantial cost‐savings when the 48 h administration of 5FU/LV in the FOLFOX regimen were to take place in an outpatient setting or be replaced by oral capecitabine as in the CAPOX regimen. This analysis based on detailed real‐life data clearly indicates that clinical choices made in oncology based on efficacy of therapy have economic consequences. Considering today's reality of finite healthcare resources, these economic consequences deserve a formal role in clinical decision making, for instance in guideline development.